(untitled) - Cox, Joyce (Redmond, WA, 2007)
The smart way to learn Office Word 2007--one step at a time! Work at your own pace through the easy numbered steps, practice files on CD, helpful hints, and troubleshooting help to master the fundamentals of working with the latest version of Word, including how to navigate the new user interface. You will discover how to use features in Word to help create, edit, and proofread documents. You'll also learn how to modify the appearance of text, organize information with tables and columns, collaborate with others, and publish documents on the Web--plus more. With STEP BY STEP, you can take just the lessons you need or work from cover to cover. Either way, you drive the instruction--building and practicing the skills you need, just when you need them! Includes a companion CD with hands-on practice files.
Keywords: Word processing,Xử lý word